2002
DOI: 10.1046/j.1365-2249.2002.02025.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of plasma cells in peripheral blood: correlation of IgE+ plasma cell frequency with IgE serum titre

Abstract: SUMMARYIn atopic patients and patients with hyper-IgE syndrome (HIE) highly elevated IgE serum levels can be detected. Due to their very low frequency little is known about IgE-producing plasma cells (PC) in peripheral blood. We used CD138 MACS microbeads to enrich plasma cells from peripheral blood of normal donors, atopic patients and one HIE patient. CD138 + cells were mainly CD45 + , CD44 ++ , CD19 dim , CD38 ++ , CD27 ++ , CD86 + , HLA-DR + / ++ , CD71 dim , VLA-4 + , VLA-5 -, CD28 -, CD25 -, CD69 -, CLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
50
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 59 publications
14
50
2
Order By: Relevance
“…16 Splenic and BM CD38 ϩϩ CD20 Ϯ B cells expressed elevated levels of CD27, CD31, and CD95 compared with naive and memory B cells (Figure 4), consistent with some recent observations on PCs in human tonsils, PB, and gut. 16,18,19,44,64 Our findings of increased CD27 expression on splenic CD38 ϩϩ CD20 Ϯ B cells were also consistent with our previous observation of intracellular IgM hi CD27 hi cells in the red pulp of human spleen. 26 Overall, based on the expression of the molecules examined in this study, the phenotype of splenic ISCs was more similar to that of tonsillar ISCs rather than ISCs detected in PB or BM.…”
Section: Discussionsupporting
confidence: 81%
“…16 Splenic and BM CD38 ϩϩ CD20 Ϯ B cells expressed elevated levels of CD27, CD31, and CD95 compared with naive and memory B cells (Figure 4), consistent with some recent observations on PCs in human tonsils, PB, and gut. 16,18,19,44,64 Our findings of increased CD27 expression on splenic CD38 ϩϩ CD20 Ϯ B cells were also consistent with our previous observation of intracellular IgM hi CD27 hi cells in the red pulp of human spleen. 26 Overall, based on the expression of the molecules examined in this study, the phenotype of splenic ISCs was more similar to that of tonsillar ISCs rather than ISCs detected in PB or BM.…”
Section: Discussionsupporting
confidence: 81%
“…8 and 9). Our finding of B cells with RV-sIg and the phenotype of ASC is in agreement with previous studies that showed that circulating B cells with intracellular Ig (ASC) also have sIg (15). Nonetheless, ASC have less sIg than B cells that do not have intracellular immunoglobulin (15).…”
Section: Cd38supporting
confidence: 82%
“…Most of our knowledge regarding the phenotype of human ASC and memory B cells comes from the study of non-antigenspecific populations (16,28,31,33). Most of these studies have been done with cells from healthy adults, adults with reactive plasmacytosis (16), allergic patients (15), and patients with autoimmunity (31). Nonetheless, the phenotype that we have described for RV ASC and memory B cells from RV-infected children is generally in agreement with these previous studies.…”
Section: Vol 78 2004 Phenotype Of Children's Rotavirus-specific B Csupporting
confidence: 78%
“…Human PC express a higher level of CD27 than memory B cells (3,6,9,14,33). Therefore, it was of interest to investigate the expression of CD27 on memory B cells cultured under conditions that induce their proliferation and differentiation to CD38 ϩ B cells, which contain a population of ISC.…”
Section: Cd27 Is Up-regulated On Activated Human Memory B Cells In VImentioning
confidence: 99%